Mining Unindustrialized Topics Based on User Mention - Thangamalar, C; Gayathri, D (International Journal of Computer Sciences and Engineering, 2025)
Social system is a place where individuals exchange and offer information related to the current events all over the world .This particular behavior of customers made us center on this logic that preparing these substance might commercial us to the extractives the current subject of interest between the users. Applying information bunching procedure like Text-Frequency-based approach over these content might leads us up to the mark in any case there will be some chance of false positives. We propose a likelihood model that can catch both ordinary specifying behavior the other hand of a customer and too the recurrence of customers occurring in their mentions. It too lives up to expectations great indeed the substance of the messages are non-printed information. The test show that the proposed mention-peculiarity based approaches can identify new points at slightest as early as text-peculiarity based approaches, and in some cases much former at the point when the subject is poorly distinguished by the printed substance in the posts.